Pemberdayaan UMKM Melalui Pembiayaan Syariah di Desa Tanjungsari - Abdillah, Iqbal; Maksum, Hary; Ahmad, Yono Ali (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Empowerment of Micro, Small and Medium Enterprises (MSMEs) is a strategic agenda in encouraging inclusive economic growth in Indonesia. This research aims to analyze the role of Islamic financing in empowering MSMEs in Tanjungsari Village. Using a qualitative approach, this study reveals that Islamic financing has a positive impact on increasing business capacity, access to capital, and community empowerment. The findings suggest that a fair and transparent sharia-based financing system can be a solution to overcome the financial constraints of MSMEs. The study also identifies challenges and strategies to strengthen Islamic financing to support the sustainability of MSMEs at the village level